Mothers’ perception and management preference of acute diarrheal disease - Terefe Keto; Yalfal Alemu; Aklilu Mamo (Intelektual Pustaka Media Utama, 2020)
Globally, diarrheal disease is one of the leading causes of morbidity and mortality among under-five years of children. Every day, approximately 2195 children die due to diarrheal diseases, which accounts for 1 in 9 child deaths worldwide. Many interventions that attempt to reduce childhood diarrhea are often fail because they are programed without understanding the problem in the target community and are culturally unsuitable. Therefore, this study aimed to assess perception and management preference of acute diarrheal disease among mothers who attend under five clinics. An institution based descriptive cross sectional study was conducted from May 1-May 30/2019. A total of 276 respondents were included in the study and consecutive sampling technique was used to identify the study participants. The results show that 47% of respondents perceive childhood diarrhea is caused by teething, 47.8% of the respondents perceive that diarrhea cannot be transmitted from one child to other. Majority of care givers prefer to give home remedies to their child, and also a substantial proportion of mothers and caregivers were not adequately knowledgeable on the use of oral rehydration salt which resulted in many of them using traditional medicine. There is need for increased health education focused on increasing caregivers‟ knowledge about the cause of diarrhea and enhancing adoption of appropriate prevention practices of diarrhea among children under five years.